Dynamics of Mixed Marriages: Analysis of Legal Choices, Divorce Recognition, and Implications For Children's Status in Indonesia - Maulida, Noor Sipa; Al Amruzi, M. Fahmi; Hafidzi, Anwar (JOURNAL OF ISLAMIC AND LAW STUDIES, 2025)
Cross-border marriages are increasingly common in the era of globalization, yet they introduce legal complexities, particularly concerning choice of law, recognition of divorce, and the status of children. Key issues that frequently arise include differences in legal systems between countries, inconsistencies in determining applicable law, challenges in recognizing foreign divorce decrees in Indonesia, and legal complications related to citizenship and child custody. This research aims to analyze the principles of choice of law, the mechanisms for divorce recognition, and their implications for the legal status of children post-divorce in cross-border marriages. This study employs a normative legal method with a statutory and conceptual approach. Primary data is sourced from Law Number 1 of 1974 concerning Marriage, Law Number 12 of 2006 concerning Citizenship, Law Number 7 of 1989 concerning Religious Courts, and Algemene Bepalingen (AB). Secondary data includes references from International Private Law, journals, and articles. Data was collected through literature review and analyzed descriptively-analytically. The research findings indicate that Indonesia adopts the principles of lex loci celebrationis, lex domicilii, and lex patriae in the choice of law for cross-border marriages, with an emphasis on Article 56 of the Marriage Law and the obligation of registration. The recognition of foreign divorces is not automatically valid in Indonesia; therefore, divorces generally must be settled through Indonesian courts based on Article 73 paragraph (3) of the Religious Courts Law and Article 18 AB. The legal status of children is highly complex due to legal vacuums in the Marriage Law regarding mixed marriages, as well as the application of the ius sanguinis principle which potentially causes children to lose Indonesian citizenship or face legalization difficulties, in addition to custody and administrative issues. Therefore, more adaptive and comprehensive legislation is urgently needed to protect the best interests of children in cross-border marriages.